Geometric Optimisation of Electroadhesive Actuators Based on 3D Electrostatic Simulation and its Experimental Verification. Issue 21 (2016) - Guo, J.; Bamber, T.; Hovell, T.; Chamberlain, M.; Justham, L.; Jackson, M.
Abstract: A systematic research methodology for the performance evaluation of different electroadhesive pad geometries is demonstrated in this paper. The proposed research method for the investigation was based on a 3D electrostatic simulation using COMSOL Multiphysics, a cost-effective electroadhesive pad design and manufacturing process based on solid-ink printing, chemical etching, conformal coating, and an advanced and mechatronic electroadhesive force testing platform and procedure. The method has been validated using 2 novel pad designs, approximate 21 cm x 19 cm, compared with the normal comb design, on the glass and aluminium plate. The experimental results showed that: 1) on the glass substrate, a relative increase of 1% and 28% in the electroadhesive forces obtainable can be seen in the curve-comb pad and the worm-comb pad respectively; and 2) on the Al substrate, a relative increase of 5% and 12% can be seen. This manifests that the two new pad designs, especially the worm-comb shape design, are better at generating larger electroadhesive forces. The comparison between the simulation results and experimental results proved that proposed method is promising for evaluating the pad design before spending time and money on pad manufacture and testing.